IMPLEMENTATION OF THE KOTAKU PROGRAM IN SLUM MANAGEMENT IN TABALONG REGENCY - Yusuf, Muhamad (Dinamika Governance: Jurnal Ilmu Administrasi Negara, 2023)
The KOTAKU program is a national program with the aim of increasing access to infrastructure and services in urban slum settlements. Tabalong Regency is one of the areas that has received the implementation of the KOTAKU Program. This study aims to analyze the implementation of the KOTAKU Program in Tabalong District with the perspective of Ripley and Franklin Compliance and What's Happening. This study uses a qualitative method. The results of this study indicate that it is not optimal and running well in the implementation of the KOTAKU Program in Tabalong Regency. The results showed that the actors involved were not yet optimal, such as several self-help groups, the clarity of the goals of the KOTAKU program which were felt to be clear and the program implementing actors in Tabalong Regency had understood the program objectives. The development of policies, coordination and communication ran smoothly and effectively, the participation of the people of Tabalong Regency was good by supporting and participating in program implementation. From the influencing factors, namely funds which are felt to have not been able to overcome the problems and the condition of the area which is quite complicated is the main obstacle.